Determinants Of Consumer Satisfaction With Processed Fish Product And Their Impact On Galeri Bahari Brand Loyalty - Purnama, Andriawan Doni; Kurniawati (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2024)
This study is to examine the influence of the blue economy on service quality, perceived quality, brand satisfaction, brand image, and WOM expressed through brand loyalty. This survey was carried out by filling out an online questionnaire. The result show that service quality, perceived quality, brand satisfaction, brand image, WOM have a positive impact on brand loyalty. Regarding suggestions for business management to further improve the blue economy in the business sector.